Authoring a Web-enhanced interface for a new language-learning environment - Dominique Hémard; Steve Cushion (Association for Learning Technology, 2000)
Computer-based applications in second language teaching have now been used for a protracted period of time, evolving from a deductive approach relying on grammatical progression to inductive methods and, more recently, exploratory interaction better suited to the constructivist mode. However, despite the initial adoption of a traditional learning environment, the first, albeit influential, generation of software design was poorly recognized, or worse, even met with scepticism by academics inasmuch as it did not seem to represent or, indeed, symbolize good teaching practices (Laurillard, 1991). As a result, original CALL programmes, such as gap-filling or substituting exercises, were often only considered appropriate as supplementary teaching material and, as such, referred to or introduced within courses as convenient adjuncts providing students with greater practical experience. Equally, students as users were never consulted on the use of CALL or, indeed, implicated beyond the designed interaction. Indeed, it was generally assumed that, since computer-based learning was a new concept, it would be, by itself, attractive and generate increased enthusiasm within the language-learning context. This situation was made even worse by a developmental process, dominated by self-taught, in-house authoring, which was too often amateurish, task-based in approach and empirical. Unfortunately, despite recent development in multimedia and hypermedia, this CALL legacy has been affecting CALL in design, practice and projected use.